Mechanically Modulated Ferromagnetism and Critical Properties of Flexible Perovskite SrRuO3 Thin Film. Issue 10 (30th June 2022) - Wang, Jing; Fan, Jiyu; Liu, Fengguang; Zu, Lin; Ma, Chunlan; Zhang, Lei; Rahman, Azizur; Wang, Caixia; Qian, Fengjiao; Hu, Dazhi; Zhu, Yan; Yang, Hao
Abstract : In an effort to explore new electronic devices with multiple functionalities, there are numerous studies of depositing perovskite oxides on flexible substrates to replace rigid silicon‐based wafer in device applications. In this study, the growth of pseudocubic SrRuO 3 single‐crystal thin film on a transparent and flexible muscovite is established. The experimental results confirm that the Curie temperature T C and the magnetic properties can be effectively tuned via the mechanical strain due to the facilitation of flexible substrate. It is found that the tensile strain increases while the compressive strain decreases the spontaneous magnetization for the thin film suffering the same ±0.24% strain. Based on the study of critical behavior, the critical exponents β   = 0.543(19) and γ   = 1.262(1) with the critical temperature T C  = 159.04(5) K and T C  = 159.10 K, respectively, are obtained by the modified Arrott plot. The set of critical exponents matches well with Widom scaling relation and the scaling equation, indicating these critical exponents are intrinsic for SrRuO3 thin films. Moreover, it is achieved that the SrRuO3 thin films exhibit a long‐range interaction coupled with 3D‐Heisenberg type. Abstract : Herein, the effect of mechanical strain, how to modulate the magnetic properties of SrRuO3 thin film deposited on flexible substrate, is studied. The finding confirms that the tensile strain increases the spontaneous magnetization while the compressive strain decreases it. This study indicates that the utilization of flexible substrate is a new effective method to modulate the physical properties of thin film.